Offloads in Rugby Union: Northern and southern hemisphere international teams - Pulling, C.; Stenning, M. (International Journal of Performance Analysis in Sport, 2015)
The aim of this study was to explore the use of offloads by northern and southern hemisphere international teams within rugby union. A total of 491 offloads were analysed from 26 international rugby union matches. The matches that were analysed were sampled from four international series': the 2012 Autumn International Series; the 2013 Autumn International Series; the 2013 Six Nations and the 2013 Rugby Championship. The northern hemisphere teams consisted of England, France, Ireland, Italy, Scotland and Wales. The southern hemisphere teams consisted of Argentina, Australia, New Zealand and South Africa. The southern hemisphere teams performed significantly more offloads during the 26 games compared to the northern hemisphere teams (U = 216.00, p = 0.02, r = -0.31). The southern hemisphere teams scored significantly more tries from the offloads performed compared to the northern hemisphere teams (U = 206.50, p = 0.01, r = -0.36) The findings suggest that southern hemisphere international teams are using the offload as an attacking strategy more effectively to score tries than northern hemisphere international teams. Future research into offloads should consider the tactics applied by the defensive team, the impact of environmental conditions and the channels of the pitch where offloads are performed.